OPAL: An open-source software tool for integrating biodiversity and ecosystem services into impact assessment and mitigation decisions. (October 2016) - Mandle, Lisa; Douglass, James; Lozano, Juan Sebastian; Sharp, Richard P.; Vogl, Adrian L.; Denu, Douglas; Walschburger, Thomas; Tallis, Heather
Abstract: Governments and financial institutions increasingly require that environmental impact assessment and mitigation account for consequences to both biodiversity and ecosystem services. Here we present a new software tool, OPAL (Offset Portfolio Analyzer and Locator), which maps and quantifies the impacts of development on habitat and ecosystem services, and facilitates the selection of mitigation activities to offset losses. We demonstrate its application with an oil and gas extraction facility in Colombia. OPAL is the first tool to provide direct consideration of the distribution of ecosystem service benefits among people in a mitigation context. Previous biodiversity-focused efforts led to redistribution or loss of ecosystem services with environmental justice implications. Joint consideration of biodiversity and ecosystem services enables targeting of offsets to benefit both nature and society. OPAL reduces the time and technical expertise required for these analyses and has the flexibility to be used across a range of geographic and policy contexts. Highlights: We present OPAL, a software tool for impact assessment and offset portfolio design. OPAL estimates impacts using metrics of biodiversity and ecosystem service provision. We demonstrate OPAL by selecting mitigation options for development in Colombia. OPAL can enhance environmental justice by revealing the consequences of development.